Prevalence of Monogenean Helminth Ectoparasites on Catfish (Clarias gariepinus) Culture Ponds in Laban Village, Menganti District, Gresik Regency, East Java Province - Sri Subekti Bendryman; Adelina Grace; Eduardus Bimo Aksono (Universitas Airlangga, 2017)
The aims of this study are to know the prevalence of monogenean helminth ecto-parasites infection on catfish culture, to know determine the number of monogenean infection on 100 samples consists of 1 and 3 months old of catfish. This study was conducted on May to June, 2011 in catfish culture ponds, Laban Village Menganti District and Gresik Regency, East Java Province. The methods were used in this research were skin and gill scrapping. The data were analyzed by using chi square test with SPSS program version 18.0 for windows. The results showed that prevalence of monogenean in catfish culture ponds, Laban Village Menganti District Gresik Regency, East Java Province was 32%. The highest infection was in the young catfish compared with the older ones with percentage of 23% and 9% respectively and based on chi square test showed that there were a very significantly differences (p < 0.01).